1993
DOI: 10.1152/ajpheart.1993.264.2.h547
|View full text |Cite
|
Sign up to set email alerts
|

alpha-Adrenergic augmentation of myogenic response in rat arterioles: role of protein kinase C

Abstract: We tested the hypothesis that protein kinase C (PKC) activation plays a major role in alpha-adrenergic augmentation of the myogenic response in rat isolated arterioles. Lumen diameter measured was with a video-monitored microscopic system. Lumen diameter did not change (131 +/- 5 vs. 126 +/- 6 microns) despite an increase in lumen pressure from 40 to 100 mmHg. Phenylephrine (Phe; 3 x 10(-7) M) augmented the myogenic response, since lumen diameter decreased significantly from 117 +/- 8 to 101 +/- 8 microns. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Because of the relatively slow time course of the myogenic vascular response (1,9,24,30), these blood pressure fluctuations will manifest themselves as VLF blood pressure variability. The mystery that constant infusions of catecholamines (45) and inhibition of the renin-angiotensin system (18,43) cause alterations in VLF blood pressure variability, even so plasma levels of catecholamines or angiotensin II are unlikely to fluctuate at very low frequencies under these experimental conditions, may be explained by the increase in myogenic vascular responsiveness elicited by catecholamines (3,41,54) and angiotensin II (19,25,47). In addition, the increase in VLF blood pressure variability observed during heat stress (51) and hypovolemia (42) may be secondary to increases in catecholamine and/or angiotensin II plasma levels under these conditions, which subsequently increase myogenic vascular responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the relatively slow time course of the myogenic vascular response (1,9,24,30), these blood pressure fluctuations will manifest themselves as VLF blood pressure variability. The mystery that constant infusions of catecholamines (45) and inhibition of the renin-angiotensin system (18,43) cause alterations in VLF blood pressure variability, even so plasma levels of catecholamines or angiotensin II are unlikely to fluctuate at very low frequencies under these experimental conditions, may be explained by the increase in myogenic vascular responsiveness elicited by catecholamines (3,41,54) and angiotensin II (19,25,47). In addition, the increase in VLF blood pressure variability observed during heat stress (51) and hypovolemia (42) may be secondary to increases in catecholamine and/or angiotensin II plasma levels under these conditions, which subsequently increase myogenic vascular responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the intensity of the myogenic vascular response to pressure can be modulated by a variety of factors. For example, it has been demonstrated that catecholamines (3,41,54) and angiotensin II (19,25,47) enhance myogenic vascular responsiveness.…”
Section: ϩmentioning
confidence: 99%
“…Furthermore, a number of studies have shown that direct submaximal stimulation of VOCs through partial depolarization with K+, which should bring these channels to their optimal working range, did not induce or augment myogenic responsiveness [8][9][10]. Other possible mechanisms involved in the myogenic response include the release of Ca2+ from intracellular stores [11] and sensitization of the contractile machinery to Ca2+, possibly via activation of protein kinase C [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown induction or augmentation of myogenic responsiveness by a-adrenoccptor agonists [8,16], proba bly due to ct|-adrenoceptor stimulation [9]. However, the cellular mechanisms involved in this induced myogenic responsiveness are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…106,107 However, 5th order rat mesenteric arteries, as well as 2nd-3rd order mouse mesenteric arteries do exhibit spontaneous myogenic tone in vitro, and the diameter-pressure curve usually has a negative slope in the pressure range from 60-120 mmHg [108][109][110] suggesting that the mesenteric arteries have the inherent capacity to autoregulate blood flow via a myogenic mechanism. As a large body of mechanistic evidence has been gathered in studies using isolated mesenteric arteries we will present data on VGCCs and the myogenic response from this vascular bed.…”
Section: Mesenteric Circulationmentioning
confidence: 99%